Dithiin functionalized metal organic framework photo-thermal material, free radical metal organic framework photo-thermal material and preparation method and application of dithiin functionalized metal organic framework photo-thermal material
Through the assembly and heat treatment of dithiain functionalized metal organic frame materials, the problem of insufficient light absorption and water transmission capacity in solar water evaporation is solved, and efficient photothermal conversion and stable solar water evaporation effect are achieved.
Patent Information
- Application Number
- CN202411229422.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-03
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2044-09-03
AI Technical Summary
In the application of solar water evaporation, existing photothermal conversion materials have problems such as limited light absorption range, poor water transmission capacity, low photothermal conversion efficiency or short service life, especially metal organic frame materials (MOFs) due to their inherent hydrophobicity. It is difficult to effectively apply to solar water evaporation.
Using dithiain functionalized metal organic frame material, the assembly of carboxyl-containing tetrathionoanthracene and tripyridylamine and trinuclear ferrite clusters forms a honeycomb hexagonal pore structure to improve the hydrophilicity and light absorption of the material. and photothermal materials with stable frames and free radicals were prepared by solvent thermal reaction and thermal annealing treatment.
The good hydrophilicity of the material and a wide light absorption range are achieved, and the efficiency of solar energy conversion into thermal energy is improved. The sulfur-containing unsaturated double bond of tetrathioanthracene provides a modification pathway, and the material exhibits extremely strong under sunlight. Photothermal conversion capability and stability.
Smart Images

Figure CN119119497A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of metal organic framework functional materials, and specifically relates to a dithiine functionalized metal organic framework photothermal material, a free radical metal organic framework photothermal material, and a preparation method and application thereof. Background Art
[0002] With the increasing consumption of traditional fossil energy and the increasing pressure on the ecological environment, accelerating the development and utilization of renewable energy solar energy has become a hot topic of global concern. The effective use of solar energy has always been a hot research field, among which photothermal conversion is a clean and efficient way to utilize solar energy. Using solar energy to achieve efficient water evaporation for seawater desalination and sewage treatment is one of the most promising sustainable freshwater production technologies, providing a new solution to the global freshwater shortage problem. Traditional water evaporation technology is mainly powered by fossil fuels, requires high energy consumption, and will produce byproducts that are harmful to the environment. Solar water evaporation technology can directly convert clean, environmentally friendly, and low-cost solar energy into thermal energy for steam generation, effectively solving the problem of water shortage.
[0003] Photothermal conversion materials (light absorbers) are the key part of solar water evaporation applications, and their performance determines the efficiency of water evaporation. In order to achieve high water evaporation rate and solar thermal conversion efficiency, ideal photothermal conversion materials should have the characteristics of wide light absorption, high solar thermal conversion efficiency, high hydrophilicity, and low thermal conductivity. At present, various photothermal conversion materials have been developed, such as carbon-based materials, metal nanoparticles, metal oxides, natural biomaterials, and polymer absorbers. However, most absorbers have problems such as limited light absorption range, poor water transmission capacity, low photothermal conversion efficiency, or short service life.
[0004] Metal-organic frameworks (MOFs) are a type of porous crystalline material formed by self-assembly of metal ions and organic ligands. They have shown many application prospects in many fields such as catalysis, gas adsorption and separation, and chemical sensing. MOFs have the advantages of clear structure, low thermal conductivity, adjustable structure, and designable functions, and are expected to provide new ideas for the development of a new generation of photothermal conversion materials with good hydrophilicity and wide light absorption. Due to the intrinsic hydrophobicity and limited light absorption of MOFs, their application as photothermal conversion materials in solar water evaporation still faces huge challenges. Summary of the invention
[0005] Based on the above reasons, the first purpose of the present invention is to provide a dithiine-functionalized metal-organic framework photothermal material, which has good hydrophilicity and a wide light absorption range; has a stable framework structure, in which the one-dimensional pore structure provides a channel for water transport; therefore, the solar energy that can be easily obtained is converted into thermal energy for water evaporation; and the presence of modifiable groups provides a way for subsequent further synthetic modification.
[0006] The second purpose of the present invention is to provide a method for preparing a dithiine-functionalized metal organic framework photothermal material.
[0007] The third object of the present invention is to provide a method for preparing a free radical metal organic framework photothermal material.
[0008] The fourth object of the present invention is to provide a free radical metal organic framework photothermal material, which has stable free radicals and can achieve excellent photothermal conversion.
[0009] The fifth purpose of the present invention is to provide an application of a material, which can be used as a photothermal conversion material for solar water evaporation.
[0010] The first object of the present invention can be achieved by adopting the following technical solutions:
[0011] A dithiine-functionalized metal-organic framework photothermal material, comprising a monomer of a structure shown in formula I, a monomer of a structure shown in formula II, and a trinuclear iron oxide cluster;
[0012] The two oxygen atoms of a carboxyl group of the monomer of the structure shown in Formula I are respectively coordinated and connected with two metal Fe atoms adjacent to a trinuclear ferrite cluster, and the two oxygen atoms of another carboxyl group are respectively coordinated and connected with two metal Fe atoms adjacent to another trinuclear ferrite cluster; six trinuclear ferrite clusters are sequentially connected through six monomers of the structure shown in Formula I to form a honeycomb hexagonal channel;
[0013] At the same time, each Fe center is hexa-coordinated by four oxygen atoms of four monomers of the structure shown in formula I, one N atom of a monomer of the structure shown in formula II, and one central μ3-O to form an octahedral structure; the trinuclear iron oxide cluster forms a 9-connected rigid network with six monomers of the structure shown in formula I and three monomers of the structure shown in formula II; wherein the N atoms of the monomer of the structure shown in formula II occupy three axial positions;
[0014] The trinuclear iron oxide cluster is centered on μ3-O, and three octahedral coordinated Fe atoms are connected with μ3-O as vertices; two adjacent Fe atoms are connected by two carboxyl oxygen groups on two ligands of the structure shown in formula I;
[0015]
[0016] The second object of the present invention can be achieved by adopting the following technical solutions:
[0017] A method for preparing a dithiino-functionalized metal-organic framework photothermal material, wherein a monomer having a structure shown in formula I, a monomer having a structure shown in formula II and an iron salt undergo solvent thermal reaction to prepare the dithiino-functionalized metal-organic framework photothermal material.
[0018] Furthermore, the molar ratio of the monomer of the structure represented by Formula I to the monomer of the structure represented by Formula II is 1:(0.9-1.2).
[0019] Furthermore, the molar ratio of the monomer of the structure shown in Formula I to the iron salt is 1:(2-2.5).
[0020] Furthermore, a mixed reagent of DMF and / or DMA and N,N-dimethylpropyleneurea is used as the solvent; the volume ratio of DMF and / or DMA to N,N-dimethylpropyleneurea is (1-4):1.
[0021] Further, the reaction is carried out at 110-140° C. for 6-72 hours.
[0022] Furthermore, the molar volume ratio of the monomer of the structure represented by Formula I to the solvent is (10-50) μmol:1 mL.
[0023] Furthermore, hexafluoroacetylacetone is added into the reaction, and the added volume of the hexafluoroacetylacetone is 1%-4% of the volume of the solvent.
[0024] Furthermore, the reaction includes a separation and washing process; after separation, the solid is washed with DMF and water; and then the solid is soaked in an acetonitrile solution for 2-4 days.
[0025] The third object of the present invention can be achieved by adopting the following technical solutions:
[0026] A method for preparing a radical metal organic framework photothermal material comprises subjecting the above-mentioned dithiine functionalized metal organic framework photothermal material to a thermal annealing reaction under an inert gas atmosphere to prepare the radical metal organic framework photothermal material.
[0027] Furthermore, the inert gas atmosphere is a nitrogen atmosphere.
[0028] Furthermore, the thermal annealing reaction conditions are: maintaining at 250-320° C. for 3-24 hours.
[0029] The fourth object of the present invention can be achieved by adopting the following technical solutions:
[0030] A free radical metal organic framework photothermal material is prepared by the above-mentioned method for preparing a free radical metal organic framework photothermal material.
[0031] The fifth object of the present invention can be achieved by adopting the following technical solutions:
[0032] Application of dithiine functionalized metal organic framework photothermal materials or free radical metal organic framework photothermal materials as photothermal conversion materials.
[0033] Furthermore, the material is loaded on a polyurethane film and water is evaporated under sunlight.
[0034] Compared with the prior art, the present invention has the following beneficial effects:
[0035] 1. A dithiine functionalized metal organic framework photothermal material of the present invention uses carboxyl-containing tetrathioanthracene and tripyridylamine as monomers, and trinuclear iron oxide clusters as metal connection sites; tetrathioanthracene is used as a connecting group to connect the trinuclear iron oxide clusters to form a ring, and tripyridylamine is further connected to Fe atoms in the ring to enhance the stability and photoelectric conversion performance of the framework. The formed MOF has good hydrophilicity and a wide light absorption range; it has a stable framework structure, and the one-dimensional pore structure therein provides a channel for water transport; therefore, the solar energy that is easily obtained is converted into thermal energy for water evaporation; and the sulfur-containing unsaturated double bond in tetrathioanthracene is used as a modifiable group, which provides a way for subsequent further synthetic modification.
[0036] 2. The preparation method of the dithiine functionalized metal organic framework photothermal material of the present invention can be prepared by solvent thermal reaction; the preparation process is simple and easy to prepare on a large scale.
[0037] 3. The free radical metal organic framework photothermal material of the present invention has strong free radical stability, exhibits a wide absorption spectrum, is conducive to the absorption of sunlight, and endows the material with extremely strong photothermal conversion capabilities.
[0038] 4. The preparation method of the free radical metal organic framework photothermal material of the present invention can be prepared by post-modification of the dithiine functionalized metal organic framework photothermal material by heat treatment. The post-synthesis modification method has simple steps, high yield and can be prepared in large quantities. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] Figure 1 Single crystal X-ray structure simulation diagrams of FeTTA-TPA, FeTTA-TPA-300 prepared in Examples and FeTTA prepared in Comparative Example 1;
[0040] Figure 2 Single crystal photographs of (a) FeTTA, (b) FeTTA-TPA and (b) FeTTA-TPA-300.
[0041] Figure 3X-ray powder diffraction diagram; (a) FeTTA-TPA single crystal simulation structure; (b) synthesized FeTTA-TPA sample; (c) FeTTA-TPA-300 sample after thermal annealing; (d) FeTTA single crystal simulation structure; (e) synthesized FeTTA sample; (f) FeTTA sample after thermal annealing at 300℃;
[0042] Figure 4 Fourier transform-infrared spectra of the organic ligand H2TTA, FeTTA-TPA and FeTTA-TPA-300 prepared in the examples, FeTTA prepared in comparative example 1, and FeTTA-300 prepared in comparative example 2;
[0043] Figure 5 Thermogravimetric analysis of FeTTA-TPA and FeTTA under nitrogen conditions;
[0044] Figure 6 Solid UV-visible absorption spectra of FeTTA, FeTTA-TPA and FeTTA-TPA-300;
[0045] Figure 7 Solid EPR test diagram of 10.0 mg of FeTTA, FeTTA-TPA and FeTTA-TPA-300 at room temperature;
[0046] Figure 8 The water contact angle test diagrams of FeTTA, FeTTA-TPA and FeTTA-TPA-300;
[0047] Fig. 9 The interface temperature variation diagram of each sample under simulated sunlight irradiation for 1 hour;
[0048] Fig.10 The graph shows the change in interfacial water evaporation mass of each sample under simulated sunlight for 1 hour. DETAILED DESCRIPTION
[0049] The technical solution of the present invention will be clearly and completely described below in conjunction with specific embodiments. Obviously, the described embodiments are only partial embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.
[0050] At present, water evaporation using MOF as a photothermal conversion material is mainly aimed at improving the hydrophilicity and light absorption range of MOF materials due to the intrinsic hydrophobicity and limited light absorption of MOF. Most of the existing MOF-based solar water evaporation systems introduce additional inorganic materials, such as composite carbon-based materials (such as graphene or carbon nanotubes) to obtain good light absorption capacity and adjustable water transport pathways. However, introducing stable free radicals into the MOF framework to transfer the charge of the overall structure and effectively reduce the band gap of the material and extend the absorption in the near-infrared region is one of the best strategies to improve the light absorption capacity. Free radical MOF not only has the characteristics of clear coordination structure, porosity and chemical stability, but also has the characteristics of free radicals, including high spin density and extended absorption in the near-infrared region, which gives free radical MOF excellent photothermal performance.
[0051] Based on the above content, the present application provides a dithiine-functionalized metal-organic framework photothermal material, a free radical metal-organic framework photothermal material, and a preparation method and application thereof.
[0052] A dithiine-functionalized metal-organic framework photothermal material, comprising a monomer of a structure shown in formula I, a monomer of a structure shown in formula II, and a trinuclear iron oxide cluster;
[0053] The two oxygen atoms of a carboxyl group of the monomer of the structure shown in Formula I are respectively coordinated and connected with two metal Fe atoms adjacent to a trinuclear ferrite cluster, and the two oxygen atoms of another carboxyl group are respectively coordinated and connected with two metal Fe atoms adjacent to another trinuclear ferrite cluster; six trinuclear ferrite clusters are sequentially connected through six monomers of the structure shown in Formula I to form a honeycomb hexagonal channel;
[0054] At the same time, each Fe center is hexa-coordinated by four oxygen atoms of four monomers of the structure shown in formula I, one N atom of a monomer of the structure shown in formula II, and one central μ3-O to form an octahedral structure; the trinuclear iron oxide cluster forms a 9-connected rigid network with six monomers of the structure shown in formula I and three monomers of the structure shown in formula II; wherein the N atoms of the monomer of the structure shown in formula II occupy three axial positions;
[0055] The molecular formula of the trinuclear iron oxide cluster is [Fe3O(COO)6], with μ3-O as the center, and three octahedrally coordinated Fe atoms connected with μ3-O as the vertex; two adjacent Fe atoms are connected by two carboxyl oxygen groups on the ligands of the structure shown in formula I.
[0056]
[0057] The monomer of the structure shown in formula I is a dithiine-functionalized carboxyl ligand (H2TTA), and the monomer of the structure shown in formula II is a pyridine-based ligand tripyridylamine (TPA), wherein H2TTA coordinates and assembles with the trinuclear ferric oxide cluster in a directed manner, and pyridine participates in the coordination to form a main framework of 9-connected highly stable trinuclear ferric oxide clusters and sulfur-containing unsaturated double bonds; it has a highly ordered three-dimensional framework stable structure, in which the formed one-dimensional pore structure provides a channel for water transport; the N group in the middle of the TPA molecule is a strong electron donor, which can increase the electron density in the MOF framework and promote the charge transfer of the overall framework; the formed MOF has good hydrophilicity and a wide light absorption range; therefore, the solar energy that is easily obtained is converted into thermal energy for water evaporation; and the sulfur-containing unsaturated double bonds in the tetrathioanthracene serve as modifiable groups, providing a path for subsequent further synthetic modifications.
[0058] The present invention discloses a method for preparing a dithiino-functionalized metal-organic framework photothermal material. A monomer having a structure shown in Formula I, a monomer having a structure shown in Formula II and an iron salt are subjected to solvent thermal reaction to prepare the dithiino-functionalized metal-organic framework photothermal material.
[0059] Solvothermal reaction is a common method for preparing MOF. In the present application, appropriate monomers of the structure shown in Formula I are selected for directed assembly with iron salts, wherein the iron atom is coordinated and connected with the oxygen on the carboxyl group of the monomer of the structure shown in Formula I in the form of a trinuclear iron oxide cluster.
[0060] The molecular formula of the trinuclear metal oxygen cluster is [Fe3O(COO)6], with μ3-O as the center, and three octahedral coordinated Fe atoms connected with μ3-O as the vertex. At the same time, each trinuclear iron oxygen cluster is connected to six monomers of the structure shown in formula I. The two oxygen atoms of the carboxyl group on each monomer of the structure shown in formula I are respectively coordinated and connected to two adjacent Fe atoms of the trinuclear metal oxygen cluster, forming a trinuclear metal oxygen cluster and forming a three-dimensional network with the structure shown in formula I. Each Fe center consists of four oxygen atoms of four TTA ligands, one The N atoms of the TPA ligands and a central μ3-O atom are hexa-coordinated to form an octahedral geometric structure.
[0061] The two oxygen atoms of a carboxyl group of the monomer of the structure shown in Formula I are respectively coordinated and connected with two metal Fe atoms adjacent to a trinuclear ferrite cluster, and the two oxygen atoms of another carboxyl group are respectively coordinated and connected with two metal Fe atoms adjacent to another trinuclear ferrite cluster; six trinuclear ferrite clusters are connected in sequence through six monomers of the structure shown in Formula I to form a cavity, forming a one-dimensional channel structure along the c-axis direction.
[0062] In particular, the N atoms of the monomer of the structure shown in Formula II occupy three axial positions and connect with the Fe of the trinuclear ferroxene cluster near the cavity, transforming a trinuclear ferroxene cluster from a 6-ligand connection to a more stable structure with 9 ligand connections, and also dividing the one-dimensional hexagonal channel along the FeTTAc axis into many pores with a length of about In addition, the coordination connection of the monomers of the structure shown in Formula II, the N group in the middle of the molecule is a strong electron donor, which can increase the electron density in the MOF framework and promote the charge transfer of the overall framework.
[0063] As one embodiment, the molar ratio of the monomer of the structure represented by Formula I to the monomer of the structure represented by Formula II is 1:(0.9-1.2).
[0064] As one embodiment, the iron salt is one or a combination of two or more of iron hydrochloride, sulfate, nitrate or hydrate thereof. Preferably, the iron salt is FeCl3·6H2O.
[0065] As one embodiment, the molar ratio of the monomer of the structure shown in Formula I to the iron salt is 1:(2-2.5). Directed assembly can be achieved by using the ligands of the above monomer and iron salt.
[0066] As one embodiment, the conditions for the solvent thermal reaction are:
[0067] A mixed reagent of DMF and / or DMA and N,N-dimethylpropyleneurea is used as a solvent; the volume ratio of DMF and / or DMA to N,N-dimethylpropyleneurea is (1-4):1.
[0068] As one embodiment, the reaction is carried out at 110-140° C. for 6-72 hours.
[0069] As one embodiment, hexafluoroacetylacetone is further added into the reaction, and the added volume of the hexafluoroacetylacetone is 1%-4% of the volume of the solvent.
[0070] As one embodiment, the molar volume ratio of the monomer of the structure shown in Formula I to the solvent is (10-50) μmol:1 mL. The conditions of the above-mentioned solvothermal reaction are selected according to the properties of the monomer and the iron salt, and the reaction temperature and time achieve a better reaction effect.
[0071] As one embodiment, the reaction includes a separation and washing process; after separation, the solid is washed with DMF and water; and then the solid is soaked in an acetonitrile solution for 2-4 days. Specifically, the single crystal sample is washed with DMF (5 mL×5) and water (5 mL×5), and then soaked in an acetonitrile solution for 2-4 days. After soaking, the solid and liquid are separated and dried in a vacuum.
[0072] The present invention also provides a method for preparing a radical metal organic framework photothermal material, wherein the dithiine functionalized metal organic framework photothermal material is subjected to a thermal annealing reaction in an inert gas atmosphere to prepare the radical metal organic framework photothermal material;
[0073]
[0074] The sulfur-containing unsaturated double bonds in the framework shrink after thermal annealing to form a framework with stable free radicals, while the original MOF only shows weak or even negligible free radical signals. The compact three-dimensional stacking structure of MOF enhances the stability of free radicals. Free radical MOF has a wide absorption spectrum, which is conducive to the absorption of sunlight, giving it a strong photothermal conversion ability.
[0075] As one embodiment, the inert gas atmosphere is a nitrogen atmosphere.
[0076] As one embodiment, the thermal annealing reaction conditions are: maintaining at 250-320° C. for 3-24 hours.
[0077] The present invention provides a radical metal organic framework photothermal material, and the radical metal organic framework photothermal material is prepared by the above-mentioned method for preparing a radical metal organic framework photothermal material.
[0078] The sulfur-containing unsaturated double bonds shrink after thermal annealing, and the compact three-dimensional stacking structure of MOF after annealing enhances the stability of free radicals. The formed free radical metal organic framework photothermal material is a framework with stable free radicals. It shows a wide absorption peak, which is conducive to the absorption of sunlight, giving it a strong photothermal conversion ability.
[0079] Application of dithiine functionalized metal organic framework photothermal materials or free radical metal organic framework photothermal materials as photothermal conversion materials.
[0080] As one embodiment, the material is loaded on a polyurethane film and water is evaporated under sunlight.
[0081] The following is a further description with reference to specific embodiments.
[0082] Example 1
[0083] 44 μmol of H2TTA, 44 μmol of TPA and 88 μmol of FeCl3·6H2O were weighed into a glass tube (8×150 mm), and 1 ml of N,N-dimethylformamide, 0.5 ml of N,N-dimethylpropylene urea and 20 uL of hexafluoroacetylacetone were added, and the mixture was then ultrasonically treated for 10 min; the glass tube was sealed with an oxyhydrogen flame and heated in an oven at 120°C for 72 h, and then naturally cooled to room temperature; the crystals were collected by filtration, and the single crystal sample was washed with DMF (5 mL×5) and water (5 mL×5), then immersed in acetonitrile solution for 3 days and dried in vacuum to obtain a dithiinothioin functionalized metal-organic framework photothermal material, named FeTTA-TPA, with a yield of 80%.
[0084] Example 2
[0085] Weigh 44 μmol of H2TTA, 39.6 μmol of TPA and 110 μmol of FeCl3 into a glass tube (8×150 mm), add 1.1 ml of N,N-dimethylformamide, 1.1 ml of N,N-dimethylacetamide, 2.2 ml of N,N-dimethylpropylene urea and 44 uL of hexafluoroacetylacetone, and then ultrasonically treat the mixture for 10 min; seal the glass tube with an oxyhydrogen flame and heat it in an oven at 140°C for 6 h, and then cool it naturally to room temperature; collect the crystals by filtration, wash the single crystal sample with DMF (5 mL×5) and water (5 mL×5), then soak it in acetonitrile solution for 3 days and dry it in vacuum to obtain a dithiinothioin functionalized metal-organic framework photothermal material, named FeTTA-TPA, with a yield of 78%.
[0086] Example 3
[0087] 44 μmol of H2TTA, 52.8 μmol of TPA and 99 μmol of FeCl3·6H2O were weighed into a glass tube (8×150 mm), and 0.7 ml of N,N-dimethylacetamide, 0.18 ml of N,N-dimethylpropylene urea and 35 uL of hexafluoroacetylacetone were added, and the mixture was then ultrasonically treated for 10 min; the glass tube was sealed with an oxyhydrogen flame and heated in an oven at 110°C for 72 h, and then naturally cooled to room temperature; the crystals were collected by filtration, and the single crystal sample was washed with DMF (5 mL×5) and water (5 mL×5), then immersed in acetonitrile solution for 3 days and dried in vacuum to obtain a dithiinothioin functionalized metal organic framework photothermal material, named FeTTA-TPA, with a yield of 75%.
[0088] Example 4
[0089] 100 mg of FeTTA-TPA was weighed and placed in aluminum foil, and then the crystals wrapped in aluminum foil were placed on a quartz boat, and the quartz boat was placed in a tube furnace; after the tube furnace was evacuated and nitrogen was passed through it three times, the temperature was raised to 300°C while nitrogen was flowing in the tube and maintained for 6 hours; after 6 hours, the quartz boat was taken out of the tube furnace and cooled to room temperature to obtain a free radical metal organic framework photothermal material, named FeTTA-TPA-300.
[0090] Example 5
[0091] 100 mg of FeTTA-TPA was weighed and placed in aluminum foil, and then the crystals wrapped in aluminum foil were placed on a quartz boat, and the quartz boat was placed in a tube furnace; after the tube furnace was evacuated and nitrogen was passed through it three times, the temperature was raised to 250°C while nitrogen was flowing in the tube for 24 hours; after 24 hours, the quartz boat was taken out of the tube furnace and cooled to room temperature to obtain a free radical metal organic framework photothermal material, named FeTTA-TPA-250.
[0092] Example 6
[0093] 100 mg of FeTTA-TPA was weighed and placed in aluminum foil, and then the crystals wrapped in aluminum foil were placed on a quartz boat, and the quartz boat was placed in a tube furnace; after the tube furnace was evacuated and nitrogen was passed through it three times, the temperature was raised to 320°C while nitrogen was flowing in the tube for 3 hours; after 3 hours, the quartz boat was taken out of the tube furnace and cooled to room temperature to obtain a free radical metal organic framework photothermal material, named FeTTA-TPA-320.
[0094] Example 7
[0095] 50 mg of FeTTA-TPA-300 powder was ultrasonically dispersed in isopropanol for 30 min. The mixed solution was evenly dropped on PU with a diameter of 2.2 cm, dried at 85°C for 1 h, and cooled to obtain FeTTA-TPA-300@PU film.
[0096] Comparative Example 1
[0097] Weigh 44 μmol H2TTA and 88 μmol FeCl3·6H2O in a glass tube (8×150 mm), add 1.5 ml N,N-dimethylformamide and 25 uL glacial acetic acid, and then ultrasonicate the mixture for 10 min; seal the glass tube with an oxyhydrogen flame and heat it in an oven at 140°C for 24 h, then cool it naturally to room temperature; collect the crystals by filtration, wash the single crystal sample with DMF (5 mL×5) and water (5 mL×5), then soak it in acetonitrile solution for 3 days, and dry it in a vacuum to obtain FeTTA crystals with a yield of 60%.
[0098] Comparative Example 2
[0099] 100 mg of FeTTA prepared in Comparative Example 1 was weighed and placed in aluminum foil, and then the crystals wrapped in aluminum foil were placed on a quartz boat, and the quartz boat was placed in a tube furnace; after the tube furnace was evacuated and nitrogen was passed through it three times, the temperature was raised to 300° C. while maintaining nitrogen flow in the tube for 6 hours; after 6 hours, the quartz boat was taken out of the tube furnace and cooled to room temperature to obtain a free radical metal organic framework photothermal material, named FeTTA-300.
[0100] Test example:
[0101] (1) Single crystal X-ray structure simulation was performed on FeTTA-TPA, FeTTA-TPA-300 prepared in Example 1 and FeTTA prepared in Comparative Example 1; the single crystal structure is as follows Figure 1 As shown, (a) FeTTA single crystal structure; (b) FeTTA-TPA single crystal structure; (c) FeTTA-TPA-300 single crystal structure; (d) TTA ligand in MOF single crystal to single crystal transformation process; single crystal photos as shown Figure 2 As shown; among them (a) FeTTA (b) FeTTA-TPA and (b) FeTTA-TPA-300.
[0102] From the results of single crystal X-ray diffraction test, it can be seen that the synthesized FeTTA framework has a one-dimensional channel of about 1nm, in which one trinuclear iron oxide cluster is connected with six TTA molecules to form a three-dimensional network. Each Fe atom adopts an octahedral coordination configuration, which is hexa-coordinated by one μ3-O atom, four carboxyl oxygen atoms of four TTA ligands and oxygen atoms from terminal solvent molecules. After the introduction of TPA, each Fe center is hexa-coordinated by four oxygen atoms of four TTAs, one N atom of TPA and one central μ3-O to form an octahedral structure; the trinuclear iron oxide cluster forms a 9-connected rigid network with six TTAs and three TPAs; the N atoms of TPA occupy three axial positions.
[0103] The single crystal structure after further thermal annealing clearly revealed the transformation of the disulfide six-membered ring to the disulfide five-membered ring in the TTA monomer, and the pyridine ligand still remained in the structure without being destroyed.
[0104] (2) X-ray powder diffraction test was performed on FeTTA-TPA and FeTTA-TPA-300 prepared in Example 1, FeTTA prepared in Comparative Example 1, and FeTTA-300 prepared in Comparative Example 2. The X-ray powder diffraction test was as follows: Figure 4 As shown; (a) FeTTA-TPA single crystal simulation structure; (b) synthesized FeTTA-TPA sample; (c) FeTTA-TPA-300 sample after thermal annealing; (d) FeTTA single crystal simulation structure; (e) synthesized FeTTA sample; (f) FeTTA sample after thermal annealing at 300℃;
[0105] Powder X-ray diffraction shows that the crystal samples obtained before and after thermal annealing of FeTTA-TPA still maintain good crystallinity, and the diffraction peak positions of FeTTA-TPA-300 and FeTTA-TPA are highly consistent, which is consistent with the single crystal simulation, indicating that the MOF material maintains the original framework after thermal annealing. However, for the FeTTA framework without TPA, its stability is poor, and the structure collapses at a temperature of 300°C, losing its original crystallinity.
[0106] (3) The organic ligand H2TTA, FeTTA-TPA and FeTTA-TPA-300 prepared in the examples, FeTTA prepared in comparative example 1 and FeTTA-300 prepared in comparative example 2 were subjected to Fourier transform infrared spectroscopy detection. The results are as follows: Figure 4 As shown, (a) organic ligand H2TTA; (b) synthesized FeTTA-TPA; (c) synthesized FeTTA-TPA-300; (d) organic ligand H2TTA; (e) synthesized FeTTA; (f) FeTTA after treatment at 300°C.
[0107] In the Fourier transform infrared spectrum of FeTTA-TPA, H2TTA was observed at about 1690 cm -1 The original carboxyl C=O stretching vibration absorption peak shifted, while the -HC=CH- stretching vibration still maintained at 3045 cm -1 At the same time, the TPA monomer was observed at about 1592 cm -1 The -C=N- stretching vibration absorption peak at 1592 cm-1 indicates that both organic ligands are successfully assembled to form FeTTA-TPA. The FeTTA-TPA-300 powder obtained by thermal annealing at 300 °C also shows a -C=N- stretching vibration absorption peak at 1592 cm-1. -1 The stretching vibration peak of -C=N- at 300℃ is eliminated, while the stretching vibration peak of -HC=CH- disappears, indicating that the unsaturated double bond in the sulfur ring successfully reacts during the heating process. The infrared spectrum of FeTTA shows that after thermal annealing at 300℃, the peak at about 1645cm -1 The carboxyl C=O stretching vibration absorption peak of TTA itself has disappeared, further confirming the collapse caused by the instability of the framework.
[0108] (4) Thermogravimetric analysis of FeTTA-TPA and FeTTA was performed under nitrogen conditions. The results are as follows Figure 5 shown.
[0109] Under nitrogen conditions, FeTTA-TPA maintains structural stability within 360°C; FeTTA loses weight significantly before 360°C and has poor thermal stability.
[0110] (5) Solid UV-visible light absorption test was performed on FeTTA, FeTTA-TPA and FeTTA-TPA-300. The UV absorption spectra were as follows: Figure 6 shown.
[0111] from Figure 6 The absorption spectrum test results show that compared with the original FeTTA, after the introduction of TPA ligands, the absorption capacity of FeTTA-TPA for light is broadened to a certain extent. The UV-Vis-NIR absorption spectrum of FeTTA-TPA-300 crystals obtained by further thermal annealing measured at room temperature shows obvious differences. FeTTA-TPA-300 powder shows a wide absorption spectrum of 200-2500nm covering the visible light and near-infrared light range, greatly enhancing the absorption of sunlight. The free radicals formed by the ring contraction in the FeTTA-TPA-300 framework produce strong intramolecular charge transfer and low band gap, which greatly improves non-radiative decay. Therefore, FeTTA-TPA-300 powder has great potential for application in solar light-heat conversion and thermoelectric conversion.
[0112] (6) Solid EPR test of 10.0 mg FeTTA, FeTTA-TPA and FeTTA-TPA-300 was performed at room temperature. The results are as follows Figure 7 shown.
[0113] FeTTA-TPA-300 solid exhibits obvious EPR signals, while the original FeTTA-TPA and FeTTA solids do not show EPR signals, indicating that FeTTA-TPA-300 of the present application has strong free radicals.
[0114] (7) The water contact angles of FeTTA, FeTTA-TPA and FeTTA-TPA-300 were tested. The water contact angles are shown in the figure below: Figure 8 shown.
[0115] from Figure 8 It can be seen that the water contact angles of FeTTA, FeTTA-TPA and FeTTA-TPA-300 are all within 90.4°. In particular, the water contact angle of the formed FeTTA-TPA is 90.4°, but after annealing at 300°C, the water contact angle of the formed FeTTA-TPA-300 is only 60.9°, showing excellent hydrophilicity.
[0116] Test example:
[0117] In order to study the solar water evaporation performance of FeTTA-TPA powder, referring to the preparation method of Example 7, 50 mg of powder sample was loaded on a polyurethane (PU) film to prepare FeTTA@PU film, FeTTA-TPA@PU film and FeTTA-TPA-300@PU film; the porous PU foam provided good thermal insulation and water transmission properties.
[0118] The PU film, FeTTA@PU film, FeTTA-TPA@PU film and FeTTA-TPA-300@PU film were placed in water and illuminated by a xenon lamp with an intensity of 0.1 W cm -2 The film was irradiated and the changes in temperature and mass were recorded within one hour. Fig. 9 The water quality changes are shown in Fig.10 shown.
[0119] from Fig. 9 It can be seen from the water evaporation interface temperature that the pure PU film reached a maximum temperature of 36°C within 20 minutes; the heating rate of the FeTTA@PU film was slower, reaching a maximum temperature of about 40°C in 40 minutes; the heating rate of the FeTTA-TPA@PU film after the introduction of TPA was significantly improved, and the maximum temperature reached about 45.6°C; and the FeTTA-TPA-300@PU film after thermal annealing had the most obvious improvement, reaching an interface temperature of 50.7°C within half an hour.
[0120] from Fig.10 It can be obtained that the water evaporation rate of FeTTA-TPA@PU foam (50 mg) is greater than that of FeTTA@PU foam (50 mg); in particular, the water evaporation rate of FeTTA-TPA-300@PU foam (50 mg) is much higher than that of FeTTA-TPA@PU and FeTTA@PU, and the interface temperature can reach 50.7 °C. It is calculated that the solar water evaporation efficiency of FeTTA-TPA-300@PU membrane reaches 98%, which is much higher than the 40% of the isomorphous MOF FeTTA@PU membrane without TPA modification.
[0121] In summary, a dithiine functionalized metal organic framework photothermal material of the present invention uses carboxyl-containing tetrathioanthracene and tripyridylamine as monomers, and trinuclear iron oxygen clusters as metal connection sites; tetrathioanthracene is used as a connecting group to connect the trinuclear iron oxygen clusters to form a ring; the N group in the middle of the tripyridylamine molecule is a strong electron donor, which increases the electron density in the MOF framework, and further connects with the Fe atom in the ring to strengthen the stability of the framework and promote the charge transfer of the overall framework. The formed MOF has good hydrophilicity and a wide light absorption range; it has a stable framework structure, and the one-dimensional pore structure therein provides a channel for water transport; therefore, the solar energy that is easily obtained is converted into heat energy for water evaporation; and the sulfur-containing unsaturated double bond in the tetrathioanthracene is used as a modifiable group. After a high-temperature deheating reaction, the formed MOF has strong free radical stability and exhibits a wide absorption spectrum, which is conducive to the absorption of sunlight, giving the material a strong photothermal conversion ability.
[0122] The above-mentioned embodiments are only preferred embodiments of the present invention and cannot be used to limit the scope of protection of the present invention. Any non-substantial changes and substitutions made by technicians in this field on the basis of the present invention shall fall within the scope of protection required by the present invention.
Claims
1. A dithiine functionalized metal organic framework photothermal material, characterized in that: Comprising a monomer having a structure shown in formula I, a monomer having a structure shown in formula II, and a trinuclear iron oxide cluster; The two oxygen atoms of a carboxyl group of the monomer of the structure shown in Formula I are respectively coordinated and connected with two metal Fe atoms adjacent to a trinuclear ferrite cluster, and the two oxygen atoms of another carboxyl group are respectively coordinated and connected with two metal Fe atoms adjacent to another trinuclear ferrite cluster; six trinuclear ferrite clusters are sequentially connected through six monomers of the structure shown in Formula I to form a honeycomb hexagonal channel; At the same time, each Fe center is hexa-coordinated by four oxygen atoms of four monomers of the structure shown in formula I, one N atom of a monomer of the structure shown in formula II, and one central μ3-O to form an octahedral structure; the trinuclear iron oxide cluster forms a 9-connected rigid network with six monomers of the structure shown in formula I and three monomers of the structure shown in formula II; wherein the N atoms of the monomer of the structure shown in formula II occupy three axial positions; The trinuclear iron oxide cluster is centered on μ3-O, and three octahedral coordinated Fe atoms are connected with μ3-O as vertices; two adjacent Fe atoms are connected by two carboxyl oxygen groups on two ligands of the structure shown in formula I; 2. A method for preparing the dithiine-functionalized metal-organic framework photothermal material according to claim 1, characterized in that: The monomer of the structure shown in formula I, the monomer of the structure shown in formula II and the iron salt react with each other through solvent thermal reaction to prepare the dithiine functionalized metal organic framework photothermal material.
3. The method for preparing the dithiine-functionalized metal-organic framework photothermal material according to claim 2, characterized in that: The molar ratio of the monomer of the structure represented by formula I to the monomer of the structure represented by formula II is 1:(0.9-1.2); The molar ratio of the monomer of the structure shown in formula I to the iron salt is 1:(2-2.5).
4. The method for preparing the dithiine-functionalized metal-organic framework photothermal material according to claim 2, characterized in that: The conditions for the solvent thermal reaction are: Using a mixed reagent of DMF and / or DMA and N,N-dimethylpropyleneurea as solvent; reacting at 110-140° C. for 6-72 hours; the volume ratio of DMF and / or DMA to N,N-dimethylpropyleneurea is (1-4):1; The molar volume ratio of the monomer of the structure represented by Formula I to the solvent is (10-50) μmol:1 mL.
5. The method for preparing the dithiine-functionalized metal-organic framework photothermal material according to claim 2, characterized in that: Hexafluoroacetylacetone is also added during the reaction, wherein the added volume of the hexafluoroacetylacetone is 1%-4% of the volume of the solvent; The reaction comprises a separation and washing process; after separation, the solid is washed with DMF and water; and then the solid is soaked in an acetonitrile solution for 2-4 days.
6. A method for preparing a radical metal organic framework photothermal material, characterized in that: The dithiine functionalized metal organic framework photothermal material according to any one of claims 1 to 5 is subjected to a thermal annealing reaction under an inert gas atmosphere to prepare the free radical metal organic framework photothermal material.
7. The method for preparing a radical metal organic framework photothermal material according to claim 6, characterized in that: The inert gas atmosphere is a nitrogen atmosphere; The conditions of the thermal annealing reaction are: 250-320° C. for 3-24 hours.
8. A free radical metal organic framework photothermal material, characterized in that: The radical metal organic framework photothermal material is prepared by the method for preparing a radical metal organic framework photothermal material according to claim 6 or 7.
9. Use of the dithiine-functionalized metal-organic framework photothermal material according to any one of claims 1 to 5 or the radical metal-organic framework photothermal material according to claim 6 or 7 as a photothermal conversion material.
10. The use according to claim 9, characterized in that: The material is supported on a polyurethane film and water is evaporated under sunlight.
Citation Information
Patent Citations
Alkynyl functionalized COF material, free radical COF material with strong electron donor-acceptor structure as well as preparation method and application of free radical COF material
CN116948123A
Metal-organic frameworks with pyrazole-based building units
CN117500377A
Photo-thermal material based on MOF (Metal Organic Framework), preparation method of photo-thermal material and solar two-stage interface evaporator
CN118027431A
Metal-organic radical framework and its preparation method
KR1020110001758A
Chemical framework compositions and methods of use
US20110137025A1
Cited By
Naphthyl-connected metal ruthenium (II) metal organic framework material, evaporator and preparation method and application of naphthyl-connected metal ruthenium (II) metal organic framework material
CN120349520A
